Development of computational fluid dynamics model for two initial CO₂ concentration in circulating fluidized bed reactor - Tanaporn Benjaprakairat; Pornpote Piumsomboon; Benjapon Chalermsinsuwan (Energy Reports, 2020)
Nowadays, the global warming is considered as a world problem because it influences the environment by increasing the average temperature of earth surface. One of the greenhouse gases that release from human activities and fossil fuels combustion in industry is CO2. Several technologies are applied to reduce the CO2 emission to atmosphere. In this study, the aim is to capture the CO2 by solid sorbent adsorption with potassium carbonate supported on gamma alumina using full loop circulating fluidized bed reactor in commercial computational fluid dynamics program, ANSYS FLUENT. This study focuses on the effect of initial CO2 concentrations from cement industry and power plant on CO2 removal efficiency. Besides, the solid volume fraction profile is also considered. The simulation results showed the hydrodynamics in circulating fluidized bed reactor that the solid sorbent was high at the reactor wall and low at the reactor center. In addition, the independent input variables were investigated which were percentage of K2CO3 loading on sorbent and gas velocity. The increasing of K2CO3 loading on sorbent and the decreasing of gas velocity increased the CO2 capture efficiency.
Keywords: 330; Cement; CFD; Circulating fluidized bed reactor; CO2 capture; K2CO3 sorbent